Impact of solar variability on the frequency variability of the Indian summer monsoon - KULKARNI, J. R.; MUJUMDAR, M.; GHARGE, S. P.; SATYAN , V.; PANT, G. B. (MAUSAM, 2001)
Earlier investigations into the epochal behavior of fluctuations in All India Summer Monsoon Rainfall (AISMR) have indicated the existence of a Low Frequency Mode (LFM) in the 60-70 years range. One of the probable sources of this variability may be due to changes in solar irradiance. To investigate this, time series of 128-year solar irradiance data from 1871-1998 has been examined. The Wavelet Transform (WT) method is applied to extract the LFM from these time series, which show a very good correspondence. A case study has been carried out to test the sensitivity of AISMR to solar irradiance. The General Circulation Model (GCM) of the Center of Ocean-Land-Atmosphere (COLA) has been integrated in the control run (using the climatological value of solar constant i.e., 1365 Wm-2) and in the enhanced solar constant condition (enhanced by 10 Wm-2) for summer monsoon season of 1986. The study shows that the large scale atmospheric circulation over the Indian region, in the enhanced solar constant scenario is favorable to good monsoon activity. A conceptual model for the impact of solar irradiance on the AISMR at LFM is also suggested.